Oral pyogenic granuloma: clinical case report - Gomes, Maira Janiely Porto (2021)
Pyogenic granuloma is a relatively common benign lesion that affects patients of all ages, being more prevalent in young adults and with a predilection for females, especially during pregnancy. Its etiology is not fully understood, but it appears to be reactional in nature. It is sually presents as an exophytic growth nodule, typically reddish in color, displaying an ulcerated surface that bleeds easily. The lesion is conventionally treated through surgical removal, and the removal of local irritant factors is paramount to reduce recurrences. This paper aims to report a Pyogenic Granuloma case diagnosed in an 18-year-old female patient who presented a lesion located in the interdental papilla, between teeth 12 and 13, with an asymptomatic evolution of about 6 months. The lesion was surgically treated and the removed material was sent to a pathological anatomy laboratory for diagnosis confirmation. Satisfactory tissue repair was observed after 30 days of postoperative follow-up, and the patient exhibited no signs of lesion recurrence for 1 year.